2016
DOI: 10.1039/c6ra04156f
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectrochemical degradation of orange II dye in wastewater at a silver–zinc oxide/reduced graphene oxide nanocomposite photoanode

Abstract: Degradation of dye monitored by visible spectrophotometry. Inset a: photocurrent response of the photoanode; inset b: proposed photoelectrochemical mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 39 publications
0
9
0
1
Order By: Relevance
“…A high‐efficiency degradation of Direct Green BE under UV–vis light was observed using Ag/LaMnO 3 –graphene as photocatalyst . Furthermore, the removal of organic pollutants can be further enhanced by photocatalysis when combining with other advanced oxidation process (AOP) such as electrochemical oxidation . Commonly, their combination is known as photoelectrochemical process.…”
Section: Antimicrobial Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…A high‐efficiency degradation of Direct Green BE under UV–vis light was observed using Ag/LaMnO 3 –graphene as photocatalyst . Furthermore, the removal of organic pollutants can be further enhanced by photocatalysis when combining with other advanced oxidation process (AOP) such as electrochemical oxidation . Commonly, their combination is known as photoelectrochemical process.…”
Section: Antimicrobial Agentsmentioning
confidence: 99%
“…Commonly, their combination is known as photoelectrochemical process. Umukoro et al have reported the higher photoelectrochemical removal efficiency on orange II dye degradation by Ag–ZnO–rGO (93%) as a photoanode material than that by ZnO–rGO (87%) and rGO (73%) electrodes …”
Section: Antimicrobial Agentsmentioning
confidence: 99%
“…The photocatalytic degradation of MG quickly reached 100% when exposed under UV light for only 15 min, while only 68% degraded by ZnO@NF, 38% by 3D RGO@NF (Figure 6b). The degradation of MG was analyzed by pseudo-first order kinetics, according to the previous reports [29,47]. The kinetic of ZnO/RGO@NF, ZnO@NF, and RGO@NF efficiency (%) on MG was studied and the degradation rate constants (k) are 0.29, 0.06, and 0.01 min −1 , respectively (Figure 6c).…”
Section: Resultsmentioning
confidence: 98%
“…RGO can also narrow the band gap and prevent nanoparticle agglomeration by providing a good dispersion of metal oxides within the composites, and thus enhance the photocatalytic efficiency [28]. Omotayo A. Arotiba et al synthesized a composite of silver (Ag), zinc oxide and RGO for efficient photoelectrochemical degradation and mineralization of organic pollutants in water treatment [29]. A quaternary TiO 2 /ZnO/RGO/Ag nanocomposite synthesized via facile microwave irradiation exhibited enhanced photoactivity for the degradation of rhodamine B under visible light [30].…”
Section: Introductionmentioning
confidence: 99%
“…9,15 TiO 2 semiconductor photoanode is the most widely used semiconductor photoanode. [14][15][16][17][18][19][20] Nevertheless, in recent years, ZnO is being utilised as an alternative to TiO 2 due to the nontoxicity, availability, low cost, chemical and thermal stability, good catalytic efficiency and optoelectronic nature of ZnO. [21][22][23][24] ZnO has also found applications in photovoltaic devices, water splitting and organic pollutants degradation.…”
Section: Introductionmentioning
confidence: 99%